Temporal variation in the allocation of acid mine drainage contaminants in the waters and sediments of the engineered remediation reed beds along the Varkenslaagte stream: an autum - winter study - Omo-Okoro, Patricia Ndidiamaka (My University, 2016)
Acid Mine Drainage (AMD) refers to the seepage or runoff of acidic water from abandoned mines into the surrounding environment. Acid mine drainage is considered a serious long term environmental threat associated with mining. This study was conducted on the Varkenslaagte canal or stream which flows from north to south within the AngloGold Ashanti West Wits gold mining operation, 75 km west of Johannesburg, and receives AMD from tailings storage facilities (TSFs) located on both the northern aspect and the western aspect of the catchment. On the Varkenslaagte, 17 reed beds were planted between 1-12-2011 and 12-9-2012, in a series of shallow excavated depressions. This study was conducted in 2013 and 2014, and aimed to ascertain: (i) whether there is any temporal difference (autumn – end of the rainy season, versus winter – mid-dry season, for 2013 and 2014 combined) in selected fresh-water quality parameters and concentrations of AMD contaminants in the flowing waters in the engineered reed beds; - this was observed, as higher concentrations were recorded in winter than in autumn, for some of the selected water quality parameters, in both survey years; (ii) to determine if vertical changes exist in the elements down the sediment profile from the surface to a depth of approximately half a metre; - conspicuous vertical changes were not evident; and also; (iii) to provide a baseline for monitoring the post clean-up state of the upper Varkenslaagte, and conclude whether the reed bed system is retaining AMD contaminants (major ions, trace and major elements). Chemical variations in water and sediment samples were measured in situ in April/May 2013 and July 2014, and water samples and sediment cores collected for laboratory analyses. Water samples were collected from three points (inflow, middle and outflow) at each of 15 reed beds (RBs, numbered RB 1 -15) in receipt of AMD from two directions (downstream and laterally from TSFs on the northern and western aspects). Ion Chromatography was used to detect chloride (Cl-) and sulphate (SO42-), Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) were used to identify major and trace elements; iron (Fe), magnesium (Mg), manganese (Mn), potassium (K), cobalt (Co), nickel (Ni), lead (Pb), copper (Cu) and zinc (Zn) in the water samples whereas X-Ray Fluorescence (XRF) analysis for elements was conducted on surface sediments (0-2cm; additional analyses of sediment core samples at depths 2-5 cm, 5-10 cm, 10-20 cm and 20 -30 cm were analyzed but were not considered further). The water in the reed beds was moderately acidic to within the target range. It ranged from pH 5.17 to 6.51 in April, 2014 (approaching the end of the wet season) (P < 0.05) (P = 0.0001) to slightly higher values of pH 5.45 to 6.82 in July, 2014 (mid-dry season) (P = 0.0053). Marginal acidity is above pH 6. A pH of 6.5 – 7.5 is within the target water quality range (TWQR) on the Highveld. High electrical conductivity (EC) values were found, ranging from 3500 – 4600 μs/cm in April and 2600 – 5500 μs/cm in July, though EC values can be higher on much of the South African gold mining Highveld. Lateral influx of AMD from the western TSFs was visually observed into two of the southernmost Varkenslaagte stream reed beds (at RBs13 and 15) during both April and July sampling. In 2014, the Varkenslaagte was still flowing from reed bed to reed bed, although very slowly, similar to 2013. Chloride, sulphate and metal concentrations were high relative to target water quality ranges in most of the reed beds in during April and July, 2014. Although higher concentrations in the sediment suggest that the reed beds are effective in capturing and retaining contaminants in sediment and root mass, the concentrations in the water in reed beds 1-15 still exceeded the target water quality ranges for aquatic ecosystems in South Africa (DWAF, 1996) and the World Health Organization (WHO) guidelines for drinking water quality (WHO, 2004). However use of the water from the Varkenslaagte by humans and livestock is prohibited by the Department of Water and Environmental Affairs, and the National Nuclear Regulator. The bar charts comparing 2013 and 2014 selected water quality data showed that during winter/drier periods with no rains, the rate of evaporation exceeded dilution; this was observed by the slightly lower pH values recorded across the reed beds in July, 2013 and 2014, in comparison with the slight higher pH values recorded across the reed beds in May, 2013 and April, 2014. The bar charts also showed that the highest EC was recorded in the winter of 2014. It was also observed from the principal component analyses (PCAs) that EC, sulphate and pH, in combination with Mg and Fe, were responsible for most of the variation in the water quality data for the two survey years, 2013 and 2014. Following the findings from this study, it is recommended that monitoring of the site should also address whether the reed beds and other control measures that have been put in place (riparian woodlands and windmill pumps) will be adequate to control the lateral seepage from the Western TSFs at some of the southernmost reed beds.
A research report submitted to the Faculty of Science, University of the Witwatersrand in partial fulfillment of the requirements for the degree of Masters (MSc. by Course work and Research Report) 30th September, 2015
Keywords: Acid mine drainage.; Sediments (Geology); Constructed wetlands.